2015
DOI: 10.3389/fpls.2015.00333
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the expression domains of a rice-specific microRNA under stress

Abstract: Plant microRNAs (miRs) have emerged as important regulators of gene expression under normal as well as stressful environments. Rice is an important cereal crop whose productivity is compromised due to various abiotic stress factors such as salt, heat and drought. In the present study, we have investigated the role of rice-specific Osa-miR820, in indica rice cultivars showing contrasting response to salt stress. The dissection of expression patterns indicated that the miR is present in all the tissues but is en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 59 publications
0
40
0
Order By: Relevance
“…The expression levels of mature miR820 were analysed using stem-loop end point PCR as described earlier [27]. Presence of miR820 was confirmed by sequencing, proving the functionality of this construct in vivo system.…”
Section: Rna Isolation and Stem-loop Reverse Transcriptase Polymerasementioning
confidence: 88%
See 3 more Smart Citations
“…The expression levels of mature miR820 were analysed using stem-loop end point PCR as described earlier [27]. Presence of miR820 was confirmed by sequencing, proving the functionality of this construct in vivo system.…”
Section: Rna Isolation and Stem-loop Reverse Transcriptase Polymerasementioning
confidence: 88%
“…While there is absolute similarity between the mature Osa-mR820 sequences, their precursor sequences share more than 90% similarity. As reported earlier the digital expression status of Osa-miR820 family, in the leaf and panicle tissues of PB1, revealed that the 24-nt species accumulated to a higher level as compared to the 21-nt species [27]. Therefore, to decipher the functional role of the 21-nt Osa-miR820 species we adopted the amiR approach, to allow its over-expression in indica rice over and above the endogenous levels.…”
Section: Construction and Validation Of Artificial Osa-mir820mentioning
confidence: 99%
See 2 more Smart Citations
“…The date palm was also characterized by the group to host a large population of conserved and novel miRNAs, functioning at the post-transcriptional level to regulate abiotic stress tolerance. Recently, Sharma et al (2015) showed a correlation between miR820 and its target de novo methyltransferase (DRM2) in the salt susceptible rice cultivar, Pusa Basmati (PB), and the salt tolerant counterpart, Pokkali (PK). Time kinetics of miR820 indicated its up-regulation in the leaves and down-regulation in the roots with increased exposure of PB and PK to salt stress.…”
Section: Recent Analyses In Model Plants and Crop Cultivarsmentioning
confidence: 99%